Specificity of Monoclonal Antibodies to Factor VIII: C - Nordfang, O; Ezban, M; Favaloro, J M; Dahl, H H M; Hansen, J J (Thrombosis and Haemostasis, 1985)
Three monoclonal antibodies (42 IgG, 47 IgG, 56 IgG) towards factor-VIII: C (VIII :C) have been produced. In ELISA for VIII:C-antigen (VIII:CAg), 47 IgG showed higher affinity for VIII: CAg than 42 IgG and 56 IgG. In solid phase immunoiso-lation of iodinated VIII :C diluted in EDTA buffer, the three monoclonals, like human VIII: C inhibitors, bound the 77/80 kD-light chain of VIII: C. In the absence of EDTA, 56 IgG bound the heavy chain-light chain complex of VIII: C, while 47 IgG was only able to bind the light chain. When coupled on Sepharose, 56 IgG adsorbed coagulation active VIII :C, while 47 IgG was only able to adsorb coagulation inactive VIII: CAg. In coagulation assay 56 IgG inhibited with 20 BU/mg while 42 IgG and 47 IgG inhibited with 4 BU/mg. A mixture of 42 IgG and 56 IgG showed a synergistic effect and inhibited with 50 BU/mg total IgG. In radioimmunoassay a human VIII: C inhibitor was able to inhibit the VIII: C binding of 42 IgG and 56 IgG but not of 47 IgG. The monoclonals did not inhibit each other. On the contrary, 56 IgG increased the binding of 42 IgG to VIII: C.
Keywords: Factor VIII :C; Monoclonal antibodies; Factor VIII antibodies; Factor VIII: CAg